Low temperature high ionic conductive zwitterionic layered solid state electrolyte and method of making same
Patent Information
- Application Number
- CN202611151295.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]本发明实施例通过提供一种低温高离子传导两性离子层状固态电解质及其制法,解决了现有技术中固态电解质中锂离子传输路径不连续、室温及低温离子传导率低以及电池循环性能不足的问题
第一,本发明的低温高离子传导两性离子层状固态电解质兼具聚合物电解质良好的成膜性和界面相容性,以及无机层状框架良好的机械稳定性和结构可调控性。与传统无机陶瓷固态电解质相比,本发明避免了陶瓷颗粒压片过程中晶界缺陷多、颗粒间接触不充分以及刚性界面接触差等问题;与传统聚合物固态电解质相比,本发明不单纯依赖聚合物链段运动进行锂离子传导,而是基于纳米片层状框架的层间通道荷电性调控,诱导两性离子载体分子有序排布,进而构筑有序、连续且稳定的离子传递通道,因此更适用于低温固态锂电池体系。
Smart Images

Figure CN122931019A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of low-temperature solid-state lithium battery technology, and in particular to a low-temperature high-ion conductivity zwitterionic layered solid electrolyte and its preparation method. Background Technology
[0002] With the rapid development of electric vehicles, aerospace, polar exploration, military equipment, and cryogenic energy storage systems, the stable operation of lithium batteries in low-temperature environments has attracted widespread attention. At low temperatures, the internal ion migration rate of the battery decreases, electrode reaction kinetics slows down, and interfacial impedance increases, leading to severe capacity decay, reduced rate performance, and even the inability to charge and discharge normally. Therefore, developing solid-state electrolytes that maintain efficient lithium-ion transport capabilities at both room temperature and low temperatures is of great significance for improving the energy output, safety, and service stability of cryogenic solid-state lithium batteries.
[0003] Solid-state lithium batteries, by using solid electrolytes instead of traditional liquid electrolytes, offer potential advantages such as reduced electrolyte leakage, volatilization, and combustion risks, suppression of lithium dendrite growth, and improved battery safety and energy density, making them a crucial development direction for next-generation high-safety energy storage devices. However, lithium-ion transport in solid electrolytes is typically limited by the internal conduction pathways of the solid phase, the material's microstructure, and the electrode / electrolyte interface contact state. Particularly at low temperatures, the ion migration capacity within the solid electrolyte further decreases, and the ion conductivity significantly reduces, becoming a key factor limiting performance improvements in low-temperature solid-state lithium batteries.
[0004] Existing solid electrolytes are mainly divided into polymer electrolytes and inorganic ceramic electrolytes. Polymer electrolytes have good film-forming properties and interfacial compatibility, and are easy to synthesize and process. However, Li in polymers... + Lithium-ion conductivity primarily relies on the chain mobility of the amorphous phase within the polymer. However, commonly used polymers have high crystallinity at room temperature, limiting chain mobility and resulting in poor ionic conductivity. When the temperature drops below 0°C, polymer chain mobility is further restricted, obstructing lithium-ion migration channels and causing a sharp decline in ionic conductivity, making it difficult to maintain effective lithium-ion conduction and failing to meet the application requirements of low-temperature solid-state lithium batteries. In contrast, inorganic ceramic electrolytes, due to their continuous lattice vacancies as Li... +Lithium-ion transport sites exhibit high theoretical ionic conductivity. However, traditional ceramic solid electrolytes are mostly prepared by pressing or sintering crystal particles. The material is prone to problems such as intergranular gaps, grain boundary defects, and insufficient particle contact, leading to discontinuous lithium-ion transport sites and resulting in actual ionic conductivity significantly lower than the theoretical value. At low temperatures, grain boundary impedance and interfacial impedance further increase, making lithium-ion migration across grain boundaries more difficult, thus exacerbating the overall decline in the ionic conductivity of the solid electrolyte. Furthermore, inorganic ceramic solid electrolytes are typically rigid, making it difficult to form sufficient and stable interfacial contact with the electrodes, easily generating large interfacial impedance, further affecting the battery's cycle performance and rate performance at low temperatures.
[0005] Therefore, developing a novel solid electrolyte with stable structure, continuous lithium-ion transport path, and excellent low-temperature ion conductivity is of great application value for improving the operating performance of low-temperature solid-state lithium batteries. Summary of the Invention
[0006] This invention provides a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte and its preparation method, which solves the problems of discontinuous lithium-ion transport paths, low ion conductivity at room temperature and low temperature, and insufficient battery cycle performance in existing solid electrolytes.
[0007] The purpose of this invention is to provide a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte, its preparation method, and its application. Compared with traditional polymer solid electrolytes and inorganic ceramic solid electrolytes, this layered solid electrolyte exhibits ordered, continuous, and stable ion transport channels, higher lithium-ion conductivity, and better electrode interface compatibility under low-temperature conditions.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A first aspect of the present invention provides a method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte, the method comprising the following steps: 1) Functional modification of two-dimensional nanosheets to prepare functionalized two-dimensional nanosheets with different charge properties; 2) A two-dimensional nanosheet layered framework membrane is prepared by self-assembly of the functionalized two-dimensional nanosheets; 3) Mix zwitterions with lithium salt in a certain proportion and confine them into the interlayer channels of the two-dimensional nanosheet layered framework membrane to obtain the low-temperature high-ion conductivity zwitterion layered solid electrolyte.
[0010] Further, step 1) includes: preparing a two-dimensional nanosheet dispersion; and functionalizing the two-dimensional nanosheets. The two-dimensional nanosheet dispersion can be obtained by dispersing directly purchased two-dimensional nanosheets, or by dispersing two-dimensional nanosheets obtained from the exfoliation of corresponding layered bulk materials using conventional methods in the prior art. Preferably, the two-dimensional nanosheet dispersion is a deionized water dispersion of nanosheets with a concentration of 1.0-5.0 mg / mL. -1 More preferably 1.0 mg / mL -1 .
[0011] Further, the functionalization modification of the two-dimensional nanosheets in step 1) is carried out through a mild silane coupling reaction, mainly including the activation of -OH groups on the nanosheet surface and silanization reaction. The activation conditions for the -OH groups on the nanosheet surface can be: 0.05-0.2 M HCl aqueous solution, preferably 0.1 M, magnetic stirring at room temperature for 4-8 hours, preferably 6 hours; the silanization reaction conditions are: ultrasonic dispersion of the silane coupling agent for 4-8 hours, preferably 6 hours; silanization reaction temperature of 40-60℃, reaction time of 4-8 hours, preferably 40℃, 8 hours.
[0012] Furthermore, the two-dimensional nanosheets include, but are not limited to, graphene oxide (GO), g-C3N4, vermiculite (Vr) nanosheets, and BN nanosheets. The two-dimensional nanosheets are preferably Vr nanosheets. The selected silane coupling agent is a molecule containing positively charged groups, negatively charged groups, and electrically neutral groups, preferably (3-aminopropyl)triethoxysilane, N-polydialkyltriethoxysilane, and 3-mercaptopropyltriethoxysilane.
[0013] Further, in step 2), a two-dimensional nanosheet layered framework membrane is prepared by vacuum filtration of the two-dimensional nanosheet dispersion. The drying conditions are 60-120℃ for 10-24h, preferably 120℃ for 12h. The thickness of the obtained two-dimensional nanosheet layered framework membrane can be 5-50μm, depending on the required thickness of the low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte membrane.
[0014] Further, step 3) includes: mixing lithium salt and zwitterion in a certain proportion and adding them to acetonitrile solvent to prepare lithium salt-zwitterion dispersion; inserting the lithium salt-zwitterion dispersion into the interlayer of the two-dimensional nanosheet layered film by temperature-controlled spin coating, and then vacuum drying to remove residual solvent.
[0015] Further, the zwitterion can be selected from [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propane)ammonium hydroxide, 3-(1-vinyl-3-imidazolium)propanesulfonate, thiobetaine 8-12, etc., preferably 3-(1-vinyl-3-imidazolium)propanesulfonate; the lithium salt can be selected from LiFSI, LiTFSI, LiBF4, preferably LiFSI or LiTFSI. The molar ratio of lithium salt to zwitterion is 1:3, 1:3.5, or 1:4, preferably 1:3.5. The amount of acetonitrile used is 10-30 mL per mole of lithium salt.
[0016] Further, in step 3), the lithium salt-zwitterionic dispersion is inserted into the interlayer of the two-dimensional nanosheet layered film via temperature-controlled spin coating. Specifically, the layered framework with the base film is attached to a temperature-controlled spin coater using double-sided adhesive. At a rotation speed of 800-1500 r / min and a temperature of 45-60℃, an automatic booster drips the prepared lithium salt-zwitterionic dispersion onto the center of the rotating nanosheet layered framework film at a certain speed, promoting uniform diffusion and distribution of lithium salt-zwitterionic ions within the layered framework channels. The preferred temperature-controlled spin coating conditions are 1000 r / min and 50℃. The spin-coated nanosheet layered film is then vacuum-dried at 60℃ for 24 h to remove residual acetonitrile solvent, thus obtaining the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte.
[0017] A second aspect of the present invention provides a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane prepared by the above-described preparation method. Preferably, the thickness of the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane is 5-30 μm, more preferably 10-20 μm.
[0018] The third aspect of the present invention provides the application of the above-described low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane in low-temperature solid-state lithium batteries.
[0019] The beneficial effects of this invention are as follows: First, the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte of the present invention combines the excellent film-forming properties and interfacial compatibility of polymer electrolytes with the good mechanical stability and structural tunability of inorganic layered frameworks. Compared with traditional inorganic ceramic solid electrolytes, the present invention avoids problems such as numerous grain boundary defects, insufficient interparticle contact, and poor rigid interface contact during ceramic particle pressing. Compared with traditional polymer solid electrolytes, the present invention does not rely solely on polymer chain segment movement for lithium-ion conduction, but rather on the charge regulation of interlayer channels within the nanosheet layered framework to induce the orderly arrangement of zwitterionic carrier molecules, thereby constructing an ordered, continuous, and stable ion transport channel. Therefore, it is more suitable for low-temperature solid-state lithium battery systems.
[0020] Secondly, the preparation method of the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte of the present invention is simple and mild, and can be achieved through steps such as functionalization modification of two-dimensional nanosheets, self-assembly into a film, and confined introduction of zwitterionic lithium salt system. This method has good operability and structural designability, and can control the charge characteristics of the layered framework, the interlayer channel environment, and the electrolyte film thickness according to actual application requirements. When the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte prepared by the present invention is applied to solid-state lithium batteries, it can effectively improve the lithium-ion conductivity, structural stability, and cycle performance of the battery under low-temperature conditions. Attached Figure Description
[0021] Figure 1 An atomic force microscope image of the functionalized nanosheets prepared according to an embodiment of the present invention; Figure 2 This is a schematic diagram illustrating the reaction principle of nanosheet functionalization modification in an embodiment of the present invention. Figure 3 The infrared spectrum of the functionalized nanosheets prepared in the embodiments of the present invention; Figure 4 Zeta potential diagram of the functionalized nanosheets prepared in the embodiments of the present invention; Figure 5 The images show the physical specimen, surface scanning electron microscope (SEM) image, cross-sectional SEM image, and elemental mapping diagram of the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane prepared according to embodiments of the present invention. Figure 6 This is a comparison chart of the ionic conductivity of the low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte membranes prepared in various embodiments of the present invention. Figure 7 The figure shows the cycle stability of a lithium-lithium symmetric battery assembled from a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane prepared according to an embodiment of the present invention. Figure 8 The figures show the charge-discharge cycle performance and efficiency-specific capacity performance of the battery assembled from the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane prepared in the embodiments of the present invention. Detailed Implementation
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0023] Example 1: Preparation of amino-functionalized low-temperature high-ionic-conductivity zwitterionic layered solid electrolyte; This embodiment prepares a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte with positively charged walls, denoted as L-ZICE-NH2, and the specific steps are as follows: (1) Preparation of vermiculite nanosheets; Vermiculite nanosheets were prepared using thermally expanded vermiculite as raw material via a two-step ion exchange method. 0.5 g of thermally expanded vermiculite crystals were added to 100 mL of saturated NaCl solution and magnetically stirred at 120 °C for 48 h. The resulting product was washed with water 3-5 times to obtain sodium-intercalated vermiculite precipitate. The sodium-intercalated vermiculite was dispersed in 100 mL of 2 M LiCl solution and magnetically stirred at 120 °C for 24 h. After washing with water 3-5 times, LiCl nanosheets were obtained. + Intercalated vermiculite precipitate. The Li + The intercalated vermiculite precipitate was dispersed in water and sonicated for 30 min; then centrifuged (8000 rpm, 10 min), and the light brown supernatant was collected to obtain the vermiculite nanosheet colloidal dispersion. The concentration of the vermiculite nanosheet colloidal dispersion was determined to be 1 mg / mL by freeze-drying. -1 .
[0024] (2) Preparation of amino-functionalized vermiculite nanosheets; Take 30 mL of the above vermiculite nanosheet suspension and disperse it in 0.1 M HCl aqueous solution. Stir magnetically at room temperature for 6 h to activate the -OH groups on the surface of the vermiculite nanosheets. Wash with water 3-5 times until the pH of the suspension is close to 7. Collect the activated vermiculite nanosheets for later use.
[0025] Take 1 mL of (3-aminopropyl)triethoxysilane (APTES) and disperse it in a water / ethanol mixture (9:1, volume ratio). Sonicate for 6 h to fully hydrolyze the APTES. Mix the activated vermiculite nanosheet suspension with the hydrolyzed APTES solution and stir at 40 °C for 8 h to carry out the silanization reaction. After the reaction, wash with water 3-5 times to remove residual APTES and impurities, obtaining an amino-functionalized vermiculite nanosheet suspension, denoted as Vr-NH2. Centrifuge the Vr-NH2 suspension (5000 rpm, 20 min) and collect the supernatant to obtain the Vr-NH2 colloidal dispersion.
[0026] (3) Preparation of low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane; Take 30 mL of the above Vr-NH2 colloidal dispersion and use a low-pressure vacuum filtration method to make the Vr-NH2 nanosheets stack up layer by layer in an orderly manner to form a vermiculite layered framework membrane; remove the membrane and dry it at room temperature for 30 min for later use.
[0027] Preparation of lithium salt-zwitterion dispersion: Dissolve LiTFSI and 3-(1-vinyl-3-imidazolium)propanesulfonate in acetonitrile at a molar ratio of 1:3.5 and stir until completely dissolved.
[0028] The vermiculite layered framework membrane with a base film was fixed onto a temperature-controlled spin coater using double-sided tape. The spin coater was set to a speed of 1000 r / min and a temperature of 50°C. An automatic booster was used to uniformly drop the lithium salt-zwitterionic dispersion onto the center of the rotating layered framework membrane, allowing the zwitterionic-lithium salt system to diffuse evenly and fill the interlayer channels of the framework. After the addition was complete, the membrane was vacuum-dried at 60°C for 24 h to remove residual acetonitrile solvent, yielding the amino-functionalized low-temperature high-ion-conductivity zwitterionic layered solid electrolyte membrane, denoted as L-ZICE-NH2.
[0029] Example 2: Preparation of methyl-functionalized low-temperature high-ionic-conductivity zwitterionic layered solid electrolyte; In this embodiment, a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte with an electrically neutral wall was prepared, denoted as L-ZICE-CH3. The preparation method was basically the same as in Example 1, except that in step (2), n-polydialkyltriethoxysilane (PTES) was used instead of APTES to prepare methyl-functionalized vermiculite nanosheets, denoted as Vr-CH3; finally, a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane with an electrically neutral wall was prepared, denoted as L-ZICE-CH3.
[0030] Example 3: Preparation of sulfonic acid-functionalized low-temperature high-ion-conductivity zwitterionic layered solid electrolyte; In this embodiment, a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte with negatively charged walls was prepared, denoted as L-ZICE-SO3H. The preparation method was basically the same as in Example 1, except that in step (2), 3-mercaptopropyltriethoxysilane (MPTES) was used instead of APTES to first prepare thiol-functionalized vermiculite nanosheets; then oxidation treatment was performed: 30 mL of thiol-functionalized vermiculite nanosheet solution was taken, 10 mL of 30 wt.% H2O2 solution was added, and after mixing evenly, the mixture was stirred at a constant temperature of 50 °C for 4 h to oxidize the thiol group (-SH) to the sulfonic acid group (-SO3H) to obtain sulfonic acid group-functionalized vermiculite nanosheets, denoted as Vr-SO3H; finally, a low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane with negatively charged walls was prepared, denoted as L-ZICE-SO3H.
[0031] Material characterization and performance testing: 1. Morphology and structural characterization of nanosheets; The three functionalized vermiculite nanosheets prepared in Examples 1-3 were characterized by atomic force microscopy (AFM), and the results are as follows: Figure 1 As shown. By Figure 1It is evident that the three functionalized nanosheets, Vr-CH3, Vr-SO3H, and Vr-NH2, all maintain a complete two-dimensional layered structure.
[0032] The reaction principle of nanosheet functionalization modification is as follows: Figure 2 As shown. Figure 2 The reaction pathways for grafting three functional groups—amino, methyl, and sulfonic acid groups—onto the surface of vermiculite nanosheets are shown, including silane coupling agent hydrolysis, condensation polymerization, and grafting reaction with hydroxyl groups on the nanosheet surface. The sulfonic acid groups are obtained by oxidizing mercapto groups with H2O2.
[0033] Three functionalized nanosheets were characterized by Fourier transform infrared spectroscopy (FT-IR), and the results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the original Vr sample is at approximately 1000 cm. -1 The characteristic absorption peaks of the Si-O-Si framework appeared at the corresponding wavenumber; the characteristic absorption peak of -CH3 appeared at the corresponding wavenumber in the Vr-CH3 sample; the characteristic absorption peaks of O=S=O and SO appeared at the corresponding wavenumber in the Vr-SO3H sample; and the characteristic absorption peaks of NH and CN appeared at the corresponding wavenumber in the Vr-NH2 sample. These results indicate that all three functional groups were successfully grafted onto the surface of vermiculite nanosheets.
[0034] Zeta potential tests were performed on three functionalized nanosheets, and the results are as follows: Figure 4 As shown. By Figure 4 As can be seen, the original Vr nanosheets are negatively charged; the surface potential of Vr-CH3 nanosheets is close to electroneutrality; the surface potential of Vr-SO3H nanosheets is even stronger negatively charged; while the surface potential of Vr-NH2 nanosheets turns positive, approximately +25 mV. This result further verifies the successful grafting of functional groups with different charge characteristics.
[0035] 2. Characterization of electrolyte membrane morphology; The low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte membranes prepared in Examples 1-3 were characterized by scanning electron microscopy (SEM), and the results are as follows: Figure 5 As shown. By Figure 5 As can be seen, the physical image on the left shows that the prepared electrolyte membrane is a uniform yellow flexible film with good mechanical integrity and processability; the SEM image of the middle surface shows that the surface of the electrolyte membrane has a dense wrinkled morphology, with a uniform structure and no obvious defects; the SEM image of the cross section on the right clearly shows a typical layered stacked structure, with a regular and orderly layered structure; together with the N and S elemental mapping diagram above, it can be seen that nitrogen and sulfur elements are uniformly distributed throughout the cross section, proving that the zwitterionic-lithium salt system has been uniformly filled into the interlayer channels of the vermiculite layered framework.
[0036] 3. Ion conductivity test; The low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte membranes prepared in Examples 1-3 were cut into 19mm diameter discs. These membranes were then assembled with two 16mm diameter, 1mm thick stainless steel gaskets in a glove box to form CR2032 coin-type blocking batteries. The impedance of the electrolyte membranes was measured using electrochemical impedance spectroscopy within a temperature range of 0-100℃, and the ionic conductivity was calculated using the following formula: ; In the formula, σ is the ionic conductivity (S cm -1 R is the bulk resistance of the electrolyte membrane (Ω); L is the thickness of the electrolyte membrane (cm); A is the effective contact area between the electrolyte membrane and the electrode (cm²). 2 ).
[0037] The test results are as follows: Under L-ZICE-NH2 conditions at 0℃, the impedance of the solid electrolyte membrane was measured to be 18.0 Ω, and the calculated lithium-ion conductivity of the solid electrolyte membrane was 6.07 × 10⁻⁶. -5 S·cm -1 At 30℃, the impedance of the solid electrolyte membrane was measured to be 6.8Ω, and the lithium-ion conductivity of the solid electrolyte membrane was calculated to be 1.6×10⁻⁶. -4 S·cm -1 The ion migration barrier is 0.20 eV.
[0038] At 0℃, the impedance of the solid electrolyte membrane (L-ZICE-CH3) was measured to be 149.8 Ω, and the calculated lithium-ion conductivity of the solid electrolyte membrane was 7.5 × 10⁻⁶. -6 S·cm -1 At 30℃, the impedance of the solid electrolyte membrane was measured to be 50.8Ω, and the calculated lithium-ion conductivity of the solid electrolyte membrane was 2.1×10⁻⁶. -5 S·cm -1 The ion migration barrier is 0.29 eV.
[0039] L-ZICE-SO3H: At 0℃, the impedance of the solid electrolyte membrane was measured to be 51.6Ω, and the calculated lithium-ion conductivity of the solid electrolyte membrane was 2.6×10⁻⁶. -5 S·cm -1 At 30℃, the impedance of the solid electrolyte membrane was measured to be 19.6Ω, and the lithium-ion conductivity of the solid electrolyte membrane was calculated to be 6.4×10⁻⁶. -5 S·cm -1 The ion migration barrier is 0.25 eV.
[0040] A comparison of the lithium-ion conductivity of the three electrolyte membranes is shown in the figure below. Figure 6 As shown. By Figure 6It is evident that the ionic conductivity of all three electrolytes increases with increasing temperature. Among them, L-ZICE-NH2 exhibits the highest ionic conductivity and the lowest ion migration activation energy at all test temperatures, indicating that the positively charged layered channel walls can effectively induce the orderly arrangement of zwitterionic carrier molecules, constructing a more efficient lithium-ion transport channel, thereby significantly improving the low-temperature ionic conductivity performance of the aforementioned low-temperature high-ionic-conductivity zwitterionic layered solid electrolyte.
[0041] 4. Battery cycle stability test; The low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane (L-ZICE-NH2) prepared in Example 1 was cut into 19mm diameter discs. Using two lithium metal sheets as electrodes, a CR2032 type coin-type lithium-lithium symmetric battery was assembled in an argon-filled glove box. The battery was tested at 25°C and a current density of 0.2mA. cm -2 Under these conditions, constant current charge-discharge cycle tests were conducted.
[0042] Test results are as follows Figure 7 As shown. By Figure 7 As can be seen, the polarization voltage of the Li|L-ZICE-NH2|Li symmetric battery is about 35mV. After 1000h of stable cycling, the voltage curve remains stable without obvious fluctuations or sudden increases. This indicates that the low-temperature, high-ion conductivity zwitterionic layered solid electrolyte membrane has excellent interfacial compatibility and structural stability with the lithium metal anode, and can effectively suppress the growth and penetration of lithium dendrites.
[0043] 5. Charge and discharge performance test; The low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane (L-ZICE-NH2) prepared in Example 1 was used as the negative electrode, and lithium iron phosphate was used as the positive electrode. A CR2032 coin cell was assembled in an argon glove box. Constant current charge-discharge cycle tests were conducted at 0°C and 0.5C rate.
[0044] Test results are as follows Figure 8 As shown. By Figure 8 As shown in the left figure, under 0℃ low-temperature conditions, the battery exhibits a high initial discharge specific capacity, and the capacity retention rate is approximately 86% after 500 cycles; Figure 8 As shown in the right figure, the charge-discharge curves from the 10th to the 500th cycle all maintain a stable voltage plateau, with slow polarization growth. These results demonstrate that the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte prepared in this invention exhibits excellent structural stability and lithium-ion conductivity under low-temperature conditions, ensuring long-term stable cycling of solid-state lithium batteries.
[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte, characterized in that, Includes the following steps: 1) Functional modification of two-dimensional nanosheets to prepare functionalized two-dimensional nanosheets with different surface charge properties; 2) The functionalized two-dimensional nanosheets are self-assembled to obtain a two-dimensional nanosheet layered framework membrane; 3) After mixing zwitterions with lithium salt, the mixture is confined and introduced into the interlayer channels of the two-dimensional nanosheet layered framework membrane. The arrangement of zwitterion carrier molecules is controlled by the charge characteristics of the layered channel walls to construct a continuous lithium ion transfer channel, thereby obtaining the low-temperature, high-ion-conductivity zwitterion layered solid electrolyte.
2. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 1, characterized in that, The two-dimensional nanosheets mentioned in step 1) are selected from one or more of graphene oxide, g-C3N4, vermiculite nanosheets, and BN nanosheets; vermiculite nanosheets are preferred.
3. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 1, characterized in that, The functionalization modification described in step 1) is achieved through a silane coupling reaction, which includes two steps: activation of hydroxyl groups on the nanosheet surface and silanization reaction. The silane coupling agent used in the silane coupling reaction is selected from one or more of silane coupling agents containing positively charged groups, silane coupling agents containing negatively charged groups, and silane coupling agents containing electrically neutral groups; preferably, one or more of (3-aminopropyl)triethoxysilane, N-polydialkyltriethoxysilane, and 3-mercaptopropyltriethoxysilane.
4. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 3, characterized in that, The conditions for hydroxyl activation are: using 0.05-0.2 M HCl aqueous solution, magnetically stirred at room temperature for 4-8 hours; the conditions for silanization reaction are: ultrasonically dispersing the silane coupling agent for 4-8 hours, and then reacting at 40-60℃ for 4-8 hours.
5. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 1, characterized in that, The self-assembly described in step 2) is carried out by vacuum filtration; the thickness of the obtained two-dimensional nanosheet layered framework membrane is 5-50 μm; the drying conditions are 60-120℃ and drying for 10-24 h.
6. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 1, characterized in that, Step 3) includes: mixing lithium salt and zwitterions in a certain proportion and dissolving them in acetonitrile solvent to prepare a lithium salt-zwitterion dispersion; introducing the lithium salt-zwitterion dispersion into the interlayer channels of a two-dimensional nanosheet layered framework film by temperature-controlled spin coating, and then vacuum drying to remove residual solvent.
7. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 1 or 6, characterized in that, The zwitterion is selected from one or more of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propane)ammonium hydroxide, 3-(1-vinyl-3-imidazolium)propanesulfonate, and thiobetaine 8-12; preferably 3-(1-vinyl-3-imidazolium)propanesulfonate; the lithium salt is selected from one or more of LiFSI, LiTFSI, and LiBF4; preferably LiFSI or LiTFSI.
8. The method for preparing a low-temperature, high-ionic-conductivity zwitterionic layered solid electrolyte according to claim 6, characterized in that, The molar ratio of the lithium salt to the zwitterionic ions is 1:3-1:4, preferably 1:3.5; the temperature-controlled spin coating process conditions are: rotation speed 800-1500 r / min, temperature 45-60℃; the vacuum drying conditions are: drying at 60℃ for 24 h.
9. A low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane, characterized in that, The invention comprises a two-dimensional nanosheet layered framework and a zwitterionic-lithium salt system confined within the interlayer channels of the layered framework; the two-dimensional nanosheet layered framework is formed by the self-assembly of surface-functionalized two-dimensional nanosheets, and the channel walls of the layered framework have tunable charge characteristics, which induce the ordered arrangement of zwitterionic carrier molecules to form continuous lithium-ion transport channels; the electrolyte membrane is prepared by the preparation method according to any one of claims 1-8, and has a thickness of 5-30 μm, preferably 10-20 μm.
10. The application of the low-temperature, high-ion-conductivity zwitterionic layered solid electrolyte membrane as described in claim 9 in low-temperature solid-state lithium batteries.